Relationship of fatigue with cognitive performance in women with early‐stage breast cancer over 2 years. Issue 5 (14th March 2019) - Gullett, Joseph M.; Cohen, Ronald A.; Yang, Gee Su; Menzies, Victoria S.; Fieo, Robert A.; Kelly, Debra L.; Starkweather, Angela R.; Jackson‐Cook, Colleen K.; Lyon, Debra E.
Abstract: Objective: Fatigue and cognitive dysfunction are major concerns for women with early‐stage breast cancer during treatment and into survivorship. However, interrelationships of these phenomena and their temporal patterns over time are not well documented, thus limiting the strategies for symptom management interventions. In this study, changes in fatigue across treatment phases and the relationship among fatigue severity and its functional impact with objective cognitive performance were examined. Methods: Participants (N = 75) were assessed at five time points beginning prior to chemotherapy to 24 months after initial chemotherapy. Fatigue severity and impact were measured on the Brief Fatigue Inventory. Central nervous system (CNS) Vital Signs was used to measure performance based cognitive testing. Temporal changes in fatigue were examined, as well as the relationship between fatigue and cognitive performance, at each time point using linear mixed effect models. Results: Severity of fatigue varied as a function of phase of treatment. Fatigue severity and its functional impact were moderate at baseline, increased significantly during chemotherapy, and returned to near baseline levels by 2 years. At each time point, fatigue severity and impact were significantly associated with diminished processing speed and complex attention performance. Conclusions: A strong association between fatigue and objective cognitive performance suggests that they are likely functionally related. That cognitive deficits were evident at baseline, whereas fatigue was more chemotherapy dependent, implicates that two symptoms share some common bases but may differ in underlying mechanisms and severity over time. This knowledge provides a basis for introducing strategies for tailored symptom management that vary over time.